The Role of Socioeconomic and Regulatory Factors in Industrial Digitalization: A Narrative Review - Indiworo, Rr. Hawik Ervina (Moneta : Journal of Economics and Finance, 2024)
This narrative review investigates the multi-dimensional nature of digital transformation in industrial sectors, focusing on regulatory policies, socioeconomic conditions, and technological innovations. The study aims to analyze the enabling and limiting factors that influence digitalization processes in both advanced and developing economies. Literature was gathered from Scopus, PubMed, and Google Scholar using keywords such as "Digital Transformation," "Industry 4.0," "SMEs," and "Blockchain," applying Boolean logic and strict inclusion-exclusion criteria. Findings indicate that proactive policies, such as state-sponsored infrastructure and digital education programs, significantly enhance industrial readiness for digital technologies. Countries like Germany and Japan demonstrate how comprehensive policy frameworks facilitate seamless adoption of innovations. In contrast, regions with inadequate infrastructure and lower digital literacy face major implementation barriers. Socioeconomic disparities further shape perceptions and outcomes of digital investments, with small enterprises often perceiving high risks and uncertain returns. Technological tools like IoT, big data, and blockchain prove instrumental in improving operational efficiency and decision-making, yet their effectiveness is context-dependent. Systemic issues such as misaligned regulations and lack of skilled labor continue to impede progress. The review underscores the urgency for integrative policies, skill development, and cross-sector collaboration to ensure equitable and effective digital transformation. It calls for future research into scalable models and policy innovations tailored to specific industrial contexts.